[Rezension von: Ashley, Susan A., 1943-, "Misfits" in Fin de siècle France and Italy] - Watson, Katherine (Crime, histoire & sociétés, 2021)
What counts as normal? That’s the question the author sets out to answer, focusing on France and Italy in the fin-de-siècle period (roughly 1870-1914), where six groups of people seemed to embody the mental and physical toll of modern life. Essentially a history of ideas about difference, the book explores the efforts of specialists and observers to identify, classify, explain and respond to aberrant and transgressive behaviours exhibited by mental misfits (geniuses, lunatics, neurotics) and ...